Method of Cultivating College Students’ Independent Learning Ability Based on Integration of Multiple Algorithm - You, Ying (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: The research on the multi-mode fusion of college students’ independent learning ability cultivation method is conducive to college students’ change of learning mode and learning thinking, improvement of the utilization rate of educational resources, and the development of the academic environment as well as the reform of the educational concept. OBJECTIVES: Aiming at the problems of college students’ current independent learning mode, such as the need for more in-depth research and the single study means. METHODS: A method for cultivating college students’ autonomous learning ability through the integration of intelligent optimization algorithms and multiple modes has been proposed. Firstly, the practices of analyzing the current college students’ autonomous learning mode and multiple learning modes are analyzed; then, using the butterfly optimization algorithm, a weight optimization method for the cultivation of college students’ independent learning ability based on the fusion of multiple modes is proposed; finally, the validity and robustness of the proposed method are verified through experimental analysis. RESULTS: The results show that the proposed method has a high cultivation effect. CONCLUSION: Solves the problem of fusion of college students’ independent learning ability cultivation modes.